Personality, motivations, and gaming disorder symptoms: A large-scale comparative study of esports players, highly engaged gamers, and recreational players. - Harshdeep S. Mangat; Róbert Urbán; Patrik Koncz; Zsolt Demetrovics; Andrea Czakó; Mark D. Griffiths; Orsolya Király (Comprehensive Psychiatry)
Background and aims: Esports playing (i.e., competitive videogaming) is an ever-growing activity but has a variety of risks or harms associated with problematic consumption. The aim of the present study was to investigate the extent to which esports is associated with different indicators of problematic consumption and how motivations for playing videogames reflect differences between esports players, recreational players, and highly engaged gamers. Methods: Self-report data were collected regarding personality, psychopathological symptoms, and gaming behavior among 14,727 gamers (mean age = 24.1 years [SD = 7.0]; 89.3 % male) comprising 557 esports players (mean age = 21.5 years [SD = 6.5]; 95.9 % male), 5101 recreational players (mean age = 26.1 years [SD = 7.5]; 87.8 % male), and 9069 highly engaged gamers (mean age = 23.2 years [SD = 6.4]; 89.7 % male). Results: Comparing all three groups, esports players were more likely to be male, younger in age, and were more likely to have a competitive personality. When compared to highly engaged gamers with regard to gaming motivation, esports players showed lower mastery, stimulation, and escapism motives. Highly engaged gamers displayed higher sensation seeking, higher negative affectivity, and lower sociability compared to the other two groups. Conclusion: Esports players tend to have a balanced psychological profile, which indicates that esports themselves are not necessarily associated with problematic use characteristics. Highly engaged gamers showed potentially harmful characteristics in terms of higher perceived stress and depression, and motivations to play (escapism). Interventions are encouraged to protect and support this group of gamers.